2022
DOI: 10.3390/v14010143
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Enterovirus D68 in Wastewater Samples from the UK between July and November 2021

Abstract: Infection with enterovirus D68 (EV-D68) has been linked with severe neurological disease such as acute flaccid myelitis (AFM) in recent years. However, active surveillance for EV-D68 is lacking, which makes full assessment of this association difficult. Although a high number of EV-D68 infections were expected in 2020 based on the EV-D68′s known biannual circulation patterns, no apparent increase in EV-D68 detections or AFM cases was observed during 2020. We describe an upsurge of EV-D68 detections in wastewat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…EV-D68 is thought to be primarily transmitted and shed in respiratory secretions; fecal shedding is less common because most strains are acid-labile and degrade in the gastrointestinal tract ( 7 ). Our study is consistent with other published studies ( 34 , 35 ) that have demonstrated that even pathogens that are predominantly shed other than in feces, such as EV-D68, can still be detected and tracked through wastewater because of the high sensitivity of that method. Our study confirms that wastewater surveillance developed for poliovirus can be extended to EV-D68 and in the future probably beyond to other known and emerging enteroviruses associated with AFM.…”
Section: Discussionsupporting
confidence: 93%
“…EV-D68 is thought to be primarily transmitted and shed in respiratory secretions; fecal shedding is less common because most strains are acid-labile and degrade in the gastrointestinal tract ( 7 ). Our study is consistent with other published studies ( 34 , 35 ) that have demonstrated that even pathogens that are predominantly shed other than in feces, such as EV-D68, can still be detected and tracked through wastewater because of the high sensitivity of that method. Our study confirms that wastewater surveillance developed for poliovirus can be extended to EV-D68 and in the future probably beyond to other known and emerging enteroviruses associated with AFM.…”
Section: Discussionsupporting
confidence: 93%
“…The highest concentration observed was 72,000 cp/g at OSP and 280,000 cp/g at SJ. A similar seasonal pattern in EVD68 in wastewater in 2022 was reported in Texas 61 , as well as in Israel 62 and the United Kingdom 63 . The study in Israel reports good agreement between wastewater concentrations of EVD68 and confirmed laboratory cases of EVD68 infections 62 .…”
supporting
confidence: 74%
“…EV-D68 was also detected from one fecal sample from a patient presenting with respiratory and diarrhea illness. Although EV-D68 detection from fecal samples is uncommon, it could provide an alternative for widespread population surveillance studies ( Corpuz et al, 2020 ; Tedcastle et al, 2022 ). It is important to note that the true burden and circulation within the community is difficult to estimate, given that community surveillance is not performed and subtype differentiation is typically only performed for severer cases following clinical consultation.…”
Section: Discussionmentioning
confidence: 99%